Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1186/s13018-018-0742-0
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Comparison of two FDA-approved interspinous spacers for treatment of lumbar spinal stenosis: Superion versus X-STOP—a meta-analysis from five randomized controlled trial studies

Abstract: BackgroundDecompressive laminectomy (DI) is a standard operation for lumbar spinal stenosis (LSS) patient with severe claudication symptoms for many years. However, patients whose symptom severity does not meet undergoing invasive surgery make therapeutic options into dilemma. Interspinous spacers (ISP) bridge the gap between surgical interventions and CC in management of LSS. In our study, we aim to systematically assess the two FDA-approved interspinous spacers for treatment of lumbar spinal stenosis: Superi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…The Editor-in-Chief has retracted this article [ 1 ] because of an error in the meta analysis. Re-examination of the data has showed that there is only one published randomized controlled trial comparing Superion with XStop.…”
Section: Retraction Notementioning
confidence: 99%
“…The Editor-in-Chief has retracted this article [ 1 ] because of an error in the meta analysis. Re-examination of the data has showed that there is only one published randomized controlled trial comparing Superion with XStop.…”
Section: Retraction Notementioning
confidence: 99%